STUDI LITERATUR : PENGARUH FAKTOR GOOD CORPORATE GOVERNANCE TERHADAP TAX AVOIDANCE - Ani Yati (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
This literature review aims to find out good corporate governance and its effect on tax avoidance in a company. This literature review uses 14 articles accredited in ministery of research and technology of the Republic Indonesia. The good corporate governance variables used are institutional ownership, independent commissioners, company size, audit committee, and audit quality. The method used is a systematic literature review. The results showed that institutional ownership, independent commissioners have no effect on tax avoidance while company size, audit committee and audit quality affect the occurrence of tax avoidance.